(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article describes the aging periods. Such as old or pre-retirement age, retirement period and the first years after retirement, period of age, long-term living in conditions of sharp deterioration of health, long-term stay with relatively good health.